The political economy of Iraq restoring balance in a post-conflict society - Gunter, Frank R.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
This groundbreaking volume offers a comprehensive look at the current state of Iraq's political economy in the aftermath of the US-led overthrow of Saddam Hussein in 2003. Frank R. Gunter describes the unique difficulties facing the modern Iraqi economy and provides detailed recommendations for fostering future economic growth and stability. The book begins with an overview of Iraq's current political, economic, and social status, including discussions of real growth, unemployment, inflation, health, poverty, education, and gender issues. This is followed by a comprehensive look at what the author identifies as the three dominant characteristics of the political economy of Iraq: corruption, political instability, and petroleum. Using these foundational ideas as a springboard, the book then provides a detailed breakdown of the Iraqi economy by sector, as well as discussions of Iraq's fiscal, monetary, and exchange rate policies. The final chapter identifies the major trends that will determine the course of future economic development in Iraq and provides insightful recommendations for encouraging positive economic growth. Offering the most comprehensive and timely discussion of Iraq's economy to date, this critical volume will appeal to students and professors of international studies, political economy, and Middle East studies as well as anyone considering doing business in this rapidly changing economy.
1. Iraq's lost decades -- 2. Population and key macroeconomic variables -- 3. Health, poverty, education, and gender issues -- 4. Corruption -- 5. Political stability and economic development -- 6. Oil and gas -- 7. Agriculture and the public distribution system -- 8. Financial intermediation -- 9. State-owned enterprises -- 10. Entrepreneurship in post-conflict Iraq -- 11. Infrastructure and essential services -- 12. International trade and finance -- 13. Fiscal, monetary, and exchange rate policy -- 14. Iraq in 2025.
Includes bibliographical references and index.
Keywords: Iraq -- Economic policy; Iraq -- Economic conditions; Electronic books